Design and Techno-Economical Optimization of Wind Turbine Generator System: Under Diverse Metrological Conditions - Mbogho, Marangi S.; Saulo, Michael J. (Journal of Technology Innovations in Renewable Energy, 2013)
The Kenyan Electricity Supply Industry (KESI) generation mix comprises; hydro-electric, geothermal, thermal and a small contribution from wind energy. Over the years, the predominant source of electricity generation in KESI has been hydro (over 60%). However, due to climate changes in recent times hydro generation has become less reliable and largely contributed to the supply–demand mismatch. Against this background there has been a paradigm shift in energy policy towards the use of Renewable Energy sources for electricity generation. Informed by this shift of policy, this paper explores the possibility of generating electrical power from wind-at Mokowe, Lamu County, in Kenya along the Indian Ocean. The paper contends that the use of optimally designed Wind Turbine Generators (WTGs) could enhance production of electrical power at the proposed site. This in effect would significantly: improve the technical and economic performance of KESI; and impact positively on the socio-economic status of the local communities at Makowe.